A comparison of various P&O algorithm in order to truck the MPPT of solar panel - Ismail Isknan; Abdellah Asbayou; Amine Aamoume; Ahmed Ihlal; Lahoussine Bouhouch (Institute of Advanced Engineering and Science, 2022)
A maximum power point track (MPPT) circuit should be used to improve and maximize photovoltaic (PV) power production. Different algorithms are proposed in the literature, and it is imperative to compare them in order to identify which MPPT approach is best for a specific application or to provide recommendations for future MPPT research. This article presents ‎‎a benchmarking of the most widely used MPPT algorithms, such as the ‎‎‎perturbation and observe classic (POC), the perturbation and improved adaptive ‎‎observer (POAM), the perturbation and observe modified (POM) as well as the ‎‎combination of the POM and POAM algorithms called PAMM. The ‎‎comparative study presented in this work will confirm that the PAMM is the ‎‎best MPPT technic to improve the performance of a PV system.‎